Redondo e sair do seu quadrado (2017): semiotic analysis of skol's advertising - posts on facebook - Vaz Camargo, Gabriella Cristina; Ribeiro, Thais Borba [UNESP] (Univ Estado Rio Grande Norte, 2020)
The main aim of this article is to investigate how the relationship between the verbal, visual and verb-visual text that composes a specific type of advertising, the post, evaluating how they work in the production of a global sense when syncretizing such languages. To this effect, the advertising posts are taken as objects of analysis in this study and understood as syncretic texts, according to Discursive Semiotics, from the contributions by Greimas (2014), Hjelmslev (1975), Floch (1985, 1986, 1995), Fiorin (2009) and Barros (2002, 2004). Three posts published on Skol's official page on Facebook were selected for the summer campaign Redondo e sair do seu passado, between December 2016 and January 2017, analyzing the verb-visual constitution marked by the superposition of verbal language (the texts written in the image and the legends of the posts) and the visual language (the figurative composition of the characters and the spaces in the images). The results of the analyzes show that the brand seeks to resize its own image and market coverage in an attempt to adopt the discourse of inclusion and breaking social standards by including among the enunciative strategies the audio description text reinforced by the hashtag #PraCegoVer.
Keywords: Figurativeness; Advertising discourse; Discursive Semiotics